2018
DOI: 10.4274/jcrpe.4810
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Retinal Nerve Fiber Layer Thickness in Non-Diabetic Obese Children and Adolescents

Abstract: Objective:Obesity affects almost all systems in the body. This includes the retinal nerve fibers which may be damaged due to a chronic inflammatory process. To determine changes in retinal nerve fiber layer (RNFL) thickness in non-diabetic children and adolescents using optical coherence tomography (OCT) and to evaluate the relationship between this change, metabolic risk factors and pubertal stage.Methods:Thirty-eight obese and 40 healthy children and adolescents aged 10-18 years were included in the study. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…Laiginhas et al observed reduced thickness in the nasal and temporal sectors of the RNFL in their cohort of obese patients, after adjusting for confounders like hypertension, dyslipidemia, and diabetes [ 9 ]. Özen et al also observed a general decrease in RNFL thickness in non-diabetic obese children and adolescents (10–18 years old), which were more reduced in the inferior quadrant, similar to our findings in our cohort of adult patients [ 20 ]. Jung et al in their population based prospective study reported that patients who are metabolically healthy and obese are at higher risk of developing POAG compared to metabolically healthy and non-obese patients, suggesting that obesity carries some risk for POAG [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Laiginhas et al observed reduced thickness in the nasal and temporal sectors of the RNFL in their cohort of obese patients, after adjusting for confounders like hypertension, dyslipidemia, and diabetes [ 9 ]. Özen et al also observed a general decrease in RNFL thickness in non-diabetic obese children and adolescents (10–18 years old), which were more reduced in the inferior quadrant, similar to our findings in our cohort of adult patients [ 20 ]. Jung et al in their population based prospective study reported that patients who are metabolically healthy and obese are at higher risk of developing POAG compared to metabolically healthy and non-obese patients, suggesting that obesity carries some risk for POAG [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…This chronic inflammation also has the potential to produce changes in the retina and macular layer (20). Indeed, previous MetS: metabolic syndrome studies have shown that obesity reduces the thickness of the retinal nerve fiber layer in children and affects choroid tissue (21,22,23). Some studies have shown that obesity leads to changes in the macular layers in children.…”
Section: Discussionmentioning
confidence: 99%
“…The RNFL and the thickness of choroid tissue can be affected by obesity. Previous studies have shown that obesity causes a thinning in RNFL thickness in children (23,24). Low level systemic inflammation is known to occur in obesity (25)(26)(27).…”
Section: Discussionmentioning
confidence: 95%